1995
DOI: 10.4319/lo.1995.40.2.0299
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dissolved organic carbon in a coastal ecosystem

Abstract: In the Bothnian Sea, there was a marked seasonal variation of dissolved organic C (DOC) in 1990-1992, with a large increase in DOC concentrations in summer at two stations. The accumulation of DOC at the coastal station persisted for 5 months, reaching peak values 24-3 1% above the mean winter value (288 PM). At the offshore station DOC concentrations were elevated throughout the water column in July, reaching 14% above the mean winter value (29 1 PM). The DOC concentration at the coastal station was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 15 publications
(17 reference statements)
10
67
1
2
Order By: Relevance
“…The insignificant effect of inorganic nutrient addition on biodegradable DOC and DON amounts suggests that the DOM degradation in the experiments was not limited by inorganic nitrogen or phosphorus availability. This is in contrast to a commonly observed stimulation of heterotrophic DOC utilization by addition of inorganic nutrients (e.g., Kuparinen and Heinänen, 1993;Zweifel et al, 1995). Neither did the addition of salt result in any significant changes in any of the study parameters.…”
Section: Doc and Don Degradationcontrasting
confidence: 49%
“…The insignificant effect of inorganic nutrient addition on biodegradable DOC and DON amounts suggests that the DOM degradation in the experiments was not limited by inorganic nitrogen or phosphorus availability. This is in contrast to a commonly observed stimulation of heterotrophic DOC utilization by addition of inorganic nutrients (e.g., Kuparinen and Heinänen, 1993;Zweifel et al, 1995). Neither did the addition of salt result in any significant changes in any of the study parameters.…”
Section: Doc and Don Degradationcontrasting
confidence: 49%
“…Zweifel et al (1995) observed a net doc accumulation in the Bothnian sea coastal areas, where bacterial community growth was limited by the phosphorus supply. in addition, doc may accumulate if bacterial growth rates remain low due to competition with algae for inorganic nutrients (thingstad et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of dissolved organic matter (DOM) in seawater exceeds by 1 to 2 orders of magnitude that of particulate organic matter, including living organisms and detritus (Williams 1995, Zweifel et al 1995. Thus, the DOM pool is potentially important in nutrition of pelagic osmotrophs, like bacteria and algae, which are capable of exploiting dissolved organic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Lignell 1990, Azam 1998, Ward & Bronk 2001, Berman & Bronk 2003. It has been suggested that accumulation of LDOC and LDON in the productive surface layer depends on temperature or nutrient availability, which control bacterial growth rates, or the semi-labile nature of freshly produced DOM (Williams 1995, Zweifel et al 1995, Thingstad & Lignell 1997, Søndergaard et al 2000. A broader scenario has also been suggested for labile DOM accumulation that would include a combination of grazing control of bacterial biomass by heterotrophic nanoflagellates and simultaneous limitation of bacterial production by either temperature (Zweifel 1999) or low mineral nutrient availability caused in turn by algal-bacterial competition for nutrients (Thingstad & Lignell 1997.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation